Overexpressing CsSABP2 enhances tolerance to Huanglongbing and citrus canker in C. sinensis - Dong, Liting; Chen, Shuang; Shang, Lanyue; Du, Meixia; Mo, Kaiqin; Pang, Shuwei; Zheng, Lin; Xu, Lanzhen; Lei, Tiangang; He, Yongrui; Zou, Xiuping (Frontiers in Plant Science, 2024)
Huanglongbing (HLB) and citrus canker, arising from Candidatus Liberibacter asiaticus (CaLas) and Xanthomonas citri pv. Citri (Xcc), respectively, have been imposing tremendous losses to the global citrus industry. Systemic acquired resistance (SAR) has been shown to be crucial for priming defense against pathogen in citrus. Salicylic acid (SA) binding protein 2 (SABP2), which is responsible for converting methyl salicylate (MeSA) to SA, is essential for full SAR establishment. Here, we characterized the functions of four citrus SABP2 genes (CsSABP2-1, CsSABP2-1 V18A , CsSABP2-2 and CsSABP2-3) against HLB and citrus canker. In vitro enzymatic assay revealed that all four proteins had MeSA esterase activities, and CsSABP2-1 and CsSABP2-1 V18A has the strongest activity. Their activities were inhibited by SA except for CsSABP2-1 V18A . Four genes controlled by a strong promoter 35S were induced into Wanjincheng orange (Citrus sinensis Osbeck) to generate transgenic plants overexpressing CsSABP2. Overexpressing CsSABP2 increased SA and MeSA content and CsSABP2-1 V18A had the strongest action on SA. Resistance evaluation demonstrated that only CsSABP2-1 V18A had significantly enhanced tolerance to HLB, although all four CsSABP2s had increased tolerance to citrus canker. The data suggested the amino acid Val-18 in the active site of CsSABP2 plays a key role in protein function. Our study emphasized that balancing the levels of SA and MeSA is crucial for regulating SAR and conferring broad-spectrum resistance to HLB and citrus canker. This finding offers valuable insights for enhancing resistance through SAR engineering.